Left atrial appendage closure: A single center experience and comparison of two contemporary devices. Issue 4 (27th August 2016) - Figini, Filippo; Mazzone, Patrizio; Regazzoli, Damiano; Porata, Giulia; Ruparelia, Neil; Giannini, Francesco; Stella, Stefano; Ancona, Francesco; Agricola, Eustachio; Sora, Nicoleta; Marzi, Alessandra; Aurelio, Andrea; et al.
Abstract : Objectives: To compare indications and clinical outcomes of two contemporary left atrial appendage (LAA) percutaneous closure systems in a "real‐world" population. Background: Percutaneous LAA occlusion is an emerging therapeutic option for stroke prevention in atrial fibrillation. Some questions however remain unanswered, such as the applicability of results of randomized trials to current clinical practice. Moreover, currently available devices have never been directly compared. Methods: We retrospectively analyzed consecutive patients who underwent LAA closure at San Raffaele Hospital, Milan, Italy between 2009 and 2015. Clinical indications and device selection were left to operators' decision; routine clinical and transesophageal echocardiography (TEE) follow‐up was performed. Results: One‐hundred and sixty‐five patients were included in the study, of which 99 were treated with the Amplatzer Cardiac Plug (ACP) and 66 with the Watchman system. During the follow‐up period (median 15 months, interquartile range 6–26 months) five patients died. The incidence of ischemic events was low, with one patient suffering a transient ischemic attack and no episodes recorded of definitive strokes. Twenty‐six leaks ≥1 mm were detected (23%); leaks were less common with the ACP and with periprocedural three‐dimensional TEE evaluation, but were not found to correlate with clinical events. Clinical outcomes were comparable between the two devices. Conclusions: Our data show excellent safety and efficacy of LAA closure, irrespectively of the device utilized, in a population at high ischemic and hemorrhagic risk. The use of ACP and 3D‐TEE minimized the incidence of residual leaks; however, the clinical relevance of small peri‐device flow warrants further investigation. © 2016 Wiley Periodicals, Inc.